Skills Required for Nursing Career Advancement: A Qualitative Study - Sheikhi; Fallahi-Khoshnab; Mohammadi; Oskouie (Kashan University of Medical Sciences, 2016)
Background Nurses require certain skills for progression in their field. Identifying these skills can provide the context for nursing career advancement. Objectives This study aimed to identify the skills needed for nurses' career advancement. Materials and Methods A qualitative approach using content analysis was adopted to study a purposive sample of eighteen nurses working in teaching hospitals affiliated with the Qazvin, Shahid Beheshti, and Iran Universities of Medical Sciences. The data were collected through semi-structured interviews, and analyzed using conventional content analysis. Results The three themes extracted from the data included interpersonal capabilities, competency for career success, and personal capacities. The results showed that acquiring a variety of skills is essential for career advancement. Conclusions The findings showed that personal, interpersonal, and functional skills can facilitate nurses' career advancement. The effects of these skills on career advancement depend on a variety of conditions that require further studies.